2016
DOI: 10.1002/pssb.201600642
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube chirality enrichment through chirality‐selective precipitation

Abstract: The interaction with surfactants changes from one carbon nanotube species to the other. We used this to replace non-ionic surfactants by ionic ones. By fine-tuning the replacement conditions, we covered some specific nanotubes with non-ionic surfactants and the others with ionic ones. Addition of salt triggers precipitation of the species suspended by the ionic surfactant; this effectively leads to chiral selective enrichment of a carbon nanotube suspension. We hence produce an (8,4)enriched suspension by repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[78]. Variation of the structure of the surfactant can induce selectivity in the interaction with the solubilized tubes [79]- [88]. Selective solubilization of the SWNTs is possible through the choice of specific DNA fragments [89], polymers [90], and copolymers [91].…”
Section: Exohedral Non-covalent Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[78]. Variation of the structure of the surfactant can induce selectivity in the interaction with the solubilized tubes [79]- [88]. Selective solubilization of the SWNTs is possible through the choice of specific DNA fragments [89], polymers [90], and copolymers [91].…”
Section: Exohedral Non-covalent Functionalizationmentioning
confidence: 99%
“…A useful comparative study on the SWNTs' isolating performances of different surfactants can be found in [76]. Variation of the structure of the surfactant can induce selectivity in its interaction with solubilized tubes [77][78][79][80][81][82][83][84][85][86]. Selective solubilization of the SWNTs is possible through the choice of specific DNA fragments [87], polymers [88], and copolymers [89].…”
Section: Exohedral Noncovalent Functionalizationmentioning
confidence: 99%